Open distance learning simulation-based virtual laboratory experiences during COVID-19 pandemic - Iza Sazanita Isa; Hasnain Abdullah; Nazirah Mohamat Kasim; Noor Azila Ismail; Zafirah Faiza (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The widespread of coronavirus disease 2019 (COVID-19) pandemic led to a discovery that open distance learning (ODL) has turned out to be the only choice for teaching and learning by most institution (s) of higher learning (IHLs). In Malaysia, ODL is considered a new approach as physical laboratory practice has always been conducted for laboratory courses. This is a quantitative study which explores the perceptions of e-Lab among the students of bachelor’s in electrical and electronic engineering (EE) by focusing on the effectiveness and readiness in conducting the e-Lab. Simulation-based model is proposed for conducting the e-Lab using an interactive media and validated with the final score performance. With the future goals of improving the e-Lab in terms of delivering methods and engaging mediums between students and laboratory instructor, this study also discovered the levels of response from students’ perception to substitute the conventional laboratory by providing an equivalent and comparable learning experiences of the students.